A New Approach for Increasing the Photocatalytic Activity of Titanium Dioxide in Water Hydrolysis - Kasapbasi, Emine Esra; Kirci, Serap; Hatipoglu, Arzu (PLEIADES PUBLISHING LTD, 2026)
Photocatalytic hydrogen production via water splitting is a sustainable and promising green technology. Producing clean hydrogen fuel using sunlight will significantly benefit the environment. TiO2 photocatalysts can split water into H-2 and O-2 under sunlight. However, the wide band gap of TiO2 (similar to 3.2 eV) limits its activity to UV-light, making it inactive under visible light. Doping with cations has been shown to enhance visible-light absorption and affect the photocatalytic properties of TiO2. Despite extensive research, there is still no clear explanation for how different cations influence its activity under solar irradiation. In this study, the non-defective anatase (001) surface was modeled using finite, neutral, stoichiometric cluster models derived from bulk anatase. Doped models were created by substituting one Ti atom with a cation, and their positions were optimized for minimum energy. Calculations were carried out using Density Functional Theory (DFT) with the B3LYP hybrid functional and the 6-31G(d) basis set. All dopants were found to reduce the TiO2 band gap, improving visible-light activity. Additionally, metal doping positively influenced water decomposition. Water showed a tendency to remain dissociated in clusters doped with +4 and +5 valence cations, indicating enhanced catalytic potential. Among these, the Ta5+-doped cluster exhibited the highest reaction energy, suggesting that future studies should focus on the reaction energetics of +5 valence doped systems to better understand their role in photocatalytic efficiency.
Keywords: TiO2; DFT; photocatalysis; water splitting; doping; OPTICAL-PROPERTIES; DOPED TIO2; DECOLORIZATION; Chemistry